Critical appraisal of contract of employment under the Nigerian legal system (2009)
Ever since the abolition of slavery, workers have become entitle to the freedom to determine what work they would warn to do and also ascertain the terms and conditions upon which their Services are being hired. Consequently, it is noted that Labour Law rest heavily upon the legal phenomenon, the individual contract of employment, in which two parties namely the employer and the individual employee are looked at by the law as equals to a legally enforceable agreement. The laws which govern employment occupy a Position of considerable importance in any modern society. This is so because of the tremendous contribution which workers can make to a national growth and development as well as the general well-being of the nation’s citizenry. In this paper we shall examine the various aspects of the contractual relationship between the employer and the employee, particularly the formation of contract of employment, rights and obligations of parties to the contract and the impact of the related legislations on the subject of discourse.